2012
DOI: 10.3109/02688697.2012.690917
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the use of intraoperative computed tomography (iCT) for image-guided placement of thoracic pedicle screws

Abstract: The iCT based spinal neuronavigation system allowed for highly safe and accurate placement (97.3%) of thoracic pedicle screws in our institution with no neurovascular injury reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…5,6 Examples of these techniques include the use of anatomic landmarks, 7 laminotomy for palpation of the pedicle, plain radiography, fluoroscopic imaging (standard or image guidance), 8,9 and CT image guidance. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Extensive literature has been published describing the technique, benefits, and drawbacks of each method, as well as comparisons between different approaches. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] With its increasing use has come a multitude of studies regarding the safety of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Examples of these techniques include the use of anatomic landmarks, 7 laminotomy for palpation of the pedicle, plain radiography, fluoroscopic imaging (standard or image guidance), 8,9 and CT image guidance. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Extensive literature has been published describing the technique, benefits, and drawbacks of each method, as well as comparisons between different approaches. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] With its increasing use has come a multitude of studies regarding the safety of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…The variability can also be explained by the free-hand method's reliance on surgeon technique preferences, not producing easily reproducible parameters for other surgeons 1 . In contrast to the free-hand method, studies illustrating the used of image-guided techniques have reported an accuracy range of 91.5% to 97.7%, overall much higher than the average accuracies reported for the free-hand technique 3,9,15,17,18,22,27 .…”
Section: Discussionmentioning
confidence: 78%
“…Free-hand approach studies reported overall accuracies for pedicle screw placement as low as 71.9%; however, the range of accuracy for PS insertion using the free-hand technique has been reported as high as 91.3% [ 3 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The huge variability in accuracy can potentially be attributed to the learning curve required to master the free-hand technique, as the procedure is generally safe for experienced surgeons but results in complications for junior surgeons [ 6 , 9 ].…”
Section: Discussionmentioning
confidence: 99%